PUSAT PENELITIAN DAN PENGEMBENGAN TANAMAN PADI DI KABUPATEN BARITO KUALA - Khollis, Ilham Nur; Tharziansyah, Muhammad (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
The Center for Rice Research and Development in Barito Kuala Regency is Kuala a place to conduct research on rice plants and the application of rice farming processes to get quality rice seeds. WithThe problem is "how to design an ecological Rice Research and Development Center in swamp agricultural land to produce adaptive superior rice seeds until they can improve the quality and quantity of rice farming in Barito Kuala Regency". By using the orientative method and applying the Concept of Ecological Architecture to solve the problem. In the end, the design of the Rice Research and Development Center in Barito Kuala Regency could be realized as a building for a research and production area for rice seeds with sufficient space facilities to carry out research and testing activities on rice plants..